Making progress in marketing research. Issue 4 (November 2017) - East, Robert; Ang, Lawrence
Highlights: Progress in disciplines requires the origination of new ideas as well as the testing of those ideas. We discuss the genesis of new ideas which often come from unpredicted findings. More emphasis on methods such as surveys may speed up the development of their marketing. Abstract: Progress in any subject requires the origination of theoretical ideas. Often, new theoretical ideas are derived from unpredicted findings. Some methods, such as surveys, yield more unpredicted findings compared to experiments and too great an emphasis on testing theories by experiment may therefore lead to fewer new ideas. We argue that researchers in marketing and other social sciences should give more consideration to methods that produce large amounts of evidence; by doing so, they may speed up the development of their subject. Chinese Abstract: 任何学科的进步都需要理论思想的出现。通常，新的理论思想来自不可预测的发现。与实验相比，某些方法，例如调查问卷，能够产生更多不可预测的发现。因此，过于注重使用实验来检验理论，可能会阻碍新思想的诞生。我们认为营销和其他社会科学研究人员应该更多地考虑能够产生大量实证的方法；这种做法能够加速学科发展与进步